The distribution of Castanea sativa and its ability to regenerate in the Czech Republic - Jaroslav Holuša; Kamil Holý (Journal of Forest Science)
Castanea sativa is a type of cultivated chestnut tree found in the Czech Republic, growing in both lowland and midland regions. These trees are usually planted individually or in pairs, with over half of the plantings located in urban areas. One-fifth of chestnut trees thrive in parks, while chestnut orchards or forest stands make up only one-tenth of the areas where chestnut trees are located. In the Czech Republic, approximately 30 ha are covered by chestnut trees. Regeneration of chestnut trees occurs in only 6% of the localities due to regular lawn mowing. However, 40% of the surveyed forests showed signs of regeneration, demonstrating the species' ability to regenerate under Central European climate conditions.